1976
DOI: 10.2527/jas1976.4251207x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Levels of Crude Protein on Performance of Growing Boars

Abstract: SUMMARYTwo trials involving 216 growing boars were conducted to study the effects of different levels of crude protein on daily gains, feed efficiency, feed intake and estimated carcass characteristics. The boars were fed either a 16, 18 or 20% crude protein ration from 23.8 to 55.8 kg (period 1). Upon completion of period 1, the protein level was reduced 2% for each treatment (14, 16 and 18%, respectively) from 55.8 to 99.6 kg (period 2).Average daily gain increased linearly (P<.01) and feed required per unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Five trials with a total of 432 Duroc, Hampshire, Yorkshire and Duroc • Hampshire boars were utilized as the complete data base for this study, although the mean performance of boars in trials 1 and 2 has been published earlier (Luce et al, 1976). In trials 1, 2 and 3, 108 boars were allotted to three treatments; 54 boars were allotted to three treatments during trials 4 and 5.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five trials with a total of 432 Duroc, Hampshire, Yorkshire and Duroc • Hampshire boars were utilized as the complete data base for this study, although the mean performance of boars in trials 1 and 2 has been published earlier (Luce et al, 1976). In trials 1, 2 and 3, 108 boars were allotted to three treatments; 54 boars were allotted to three treatments during trials 4 and 5.…”
Section: Methodsmentioning
confidence: 99%
“…Protein levels in the diet were reduced for each pen individually as the averaged 54.4 kg and boars removed from test weekly as kg. Ultrasonic estimates of boars in the pen were individually they reached 100 backfat thickness and longissimus muscle area were obtained as described by Luce et al (1976).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Feed/ gain was lower (P<.05) during the growing phase for pigs fed the higher sequence and overall favored (P<.10) pigs fed the higher sequence. Speer et al (1957), Creswell et al (1975) and Luce et al (1976) reported improved daily gain and reduced feed per unit of gain when boars were fed protein at levels higher than suggested by the NRC for barrows and gilts. Reinhard et al (1976), in a study of boars, gilts and barrows during the growing phase, and Fammatre et al (1977), in a trial with barrows and gilts in the finishing phase, found no improvement in growth rate and feed/ gain when higher-than-NRC-suggested protein levels were fed.…”
Section: Resultsmentioning
confidence: 99%